2002
DOI: 10.1093/bja/88.3.369
|View full text |Cite
|
Sign up to set email alerts
|

Noise in the postanaesthesia care unit

Abstract: Even though sound in the PACU exceeded the internationally recommended intensity (40 dBA), it did not cause discomfort. Conversation was the most common cause of excess noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 26 publications
1
37
1
2
Order By: Relevance
“…Thus, routine activities of healthcare professionals have been identified as a potential source of noise. The need to elevate the level of speech to overcome the noisy environment in the NICU, thereby increasing the negative impacts on staff, newborns, and their ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 13 families, is another concern. High noise levels are associated with an increased rate of errors and accidents, leading to a performance decrease among staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, routine activities of healthcare professionals have been identified as a potential source of noise. The need to elevate the level of speech to overcome the noisy environment in the NICU, thereby increasing the negative impacts on staff, newborns, and their ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 13 families, is another concern. High noise levels are associated with an increased rate of errors and accidents, leading to a performance decrease among staff.…”
Section: Discussionmentioning
confidence: 99%
“…More information regarding auditory and non-auditory health effects of noise has been reported by Basner et al [5]. Furthermore, noise as a stressor does not only influence negatively the healing process of patients (in this case premature infants) but also puts pressure on the workers which can result in a higher error occurrence [12][13][14]. In fact, there has been very little research on the influences of acoustic conditions on healthcare staff [15].…”
Section: Introductionmentioning
confidence: 99%
“…newborn's ears and equidistant from the walls of the incubator to simulate the infants' exposure [14]. Although no infant was in incubator during testing, several folded neonatal blankets were used to support the noise dosimeter.…”
Section: Methodsmentioning
confidence: 99%
“…However, Allaouchiche et al (2002) found staff conversation caused 56 % of sounds greater than 65 dB and other noise sources (alarm, telephone, nursing care) were each less than 10 % of these sounds. A review article reported by Ulrich and Zimring (2004) indicated that many studies have shown that noise levels in most hospitals in USA are much higher.…”
Section: Introductionmentioning
confidence: 91%